Student Participants’ Views of Mathematics Content Representation within Selected Alabama State FFA Career Development Events - Wells, Trent; Anderson, Ryan G.; Parr, Brian A. (Journal of Agricultural Systems, Technology, and Management, 2015)
This study sought to examine students’ perceptions of mathematics content integration in one of the most popular activities offered to agricultural education students, Career Development Events (CDEs). Data were collected from students participating in the Alabama State FFA Agricultural Mechanics, Forestry, Floriculture, and Nursery/Landscape CDEs (n = 160). Participants indicated positive attitudes toward utilizing agriculture as a context for teaching mathematics content. Conceivably, a “saturation point” of mathematics integration into agricultural education curricula may not have yet been reached. The researchers recommend that math and agricultural education teachers form communities of practice to enhance student achievement in mathematics and agricultural education. This study should be replicated utilizing students participating in national-level CDEs to determine if congruency exists with these results. Real-world competition coupled with enhanced academics in agricultural curricula can help to prepare a competent and capable agricultural workforce equipped to face tomorrow’s challenges.